Persepsi Mahasiswa Terhadap Minat Investasi Pada Saham Syariah (Studi Kasus Mahasiswa Jurusan Manajemen Fakultas Ekonomi Dan Ilmu Sosial UIN Suska Riau) - Sari, Maya Rizki; Tinaria, Lisa (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to determine the effect of Perceptions of Sharia Compliance, Perceptions of Investment Objectives and Perceptions of Risk on Investment Interest in Management Major Students of the Faculty of Economics and Social Sciences, State Islamic University of Sultan Syarif Kasim Riau, either partially or simultaneously. The data used in this study is primary data obtained from the results of filling out questionnaires for 100 respondents. Data collection methods in this study used questionnaires, literature books and journals related to research. Data analysis methods used include descriptive analysis, data quality test, classical assumption test, multiple regression analysis and hypothesis testing. The results of this study indicate that partially Perceived Investment Purpose and Perceived Risk have a positive and significant effect on Investment Interest, while partially Perception of Sharia Compliance has no effect and is not significant on Investment Interest. The results of simultaneous testing of the influence of Perceived Sharia Compliance, Perceived Investment Objectives and Perceived Risk have a positive and significant influence on Sharia Investment Interest. The value of Adjusted R Square is 0.326 or 32.6% which means that Investment Interest is influenced by Perceived Sharia Compliance, Perceived Investment Purpose and Perceived Risk and the remaining 67.4% can be explained by other factors not examined in this study.